USING THE KPI SYSTEM IN ASSESSING PRODUCTION EFFICIENCY IN RAILWAY TRANSPORT ENTERPRISES (Marketing Journal, 2025)
This study examines the impact of implementing a Key Performance Indicators (KPI) system on the production efficiency of railway transport enterprises. The theoretical foundations of the KPI system, its application in the railway sector, and its role in en hancing operational efficiency are analyzed. An empirical analysis was conducted based on the Data Envelopment Analysis (DEA) method and the Overall Equipment Effectiveness (OEE) methodology. The study provides practical recommendations for implementing a KPI system for railway transport companies.
Keywords: KPI; railway transport; production efficiency; Data Envelopment Analysis (DEA); Overall Equipment Effectiveness (OEE); operational indicators; rolling stock; benchmarking. № 1 291